2017
DOI: 10.1016/j.jeconom.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Fractional order statistic approximation for nonparametric conditional quantile inference

Abstract: Using and extending fractional order statistic theory, we characterize the O(n −1 ) coverage probability error of the previously proposed confidence intervals for population quantiles using L-statistics as endpoints in Hutson (1999). We derive an analytic expression for the n −1 term, which may be used to calibrate the nominal coverage level to get O n −3/2 [log(n)] 3 coverage error. Asymptotic power is shown to be optimal. Using kernel smoothing, we propose a related method for nonparametric inference on cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(44 citation statements)
references
References 42 publications
2
42
0
Order By: Relevance
“…The accuracy of each new unconditional CI is precisely characterized in terms of coverage error, defined as the difference between the true and nominal coverage probabilities. The foundation of our methods' high‐order accuracy is the use of the probability integral transform and a Dirichlet (instead of Gaussian) approximation of the distribution of a linear combination of ‘fractional'‐order statistics (linearly interpolated between observed order statistics), formally studied in Goldman and Kaplan (, hereafter GK). For our confidence set for a vector of quantiles, the Dirichlet approximation is the only source of error, so coverage error is O(n1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of each new unconditional CI is precisely characterized in terms of coverage error, defined as the difference between the true and nominal coverage probabilities. The foundation of our methods' high‐order accuracy is the use of the probability integral transform and a Dirichlet (instead of Gaussian) approximation of the distribution of a linear combination of ‘fractional'‐order statistics (linearly interpolated between observed order statistics), formally studied in Goldman and Kaplan (, hereafter GK). For our confidence set for a vector of quantiles, the Dirichlet approximation is the only source of error, so coverage error is O(n1).…”
Section: Introductionmentioning
confidence: 99%
“…The acronyms used include those for [conditional] interquantile range ([C]IQR), [conditional] quantile difference ([C]QD), [conditional] quantile treatment effect ([C]QTE), confidence interval (CI), confidence set (CS), coverage probability (CP), coverage probability error (CPE), cumulative distribution function (CDF), mean squared error (MSE), mean value theorem (MVT), and probability density function (PDF), and GK denotes Goldman and Kaplan (). Notationally, Beta(a,b) is a beta distribution with parameters a and b , or such a random variable if clear from context, and Dir(k1,k2,) is a Dirichlet distribution (or random variable); Φ(·) and φ(·) are the standard normal CDF and PDF, respectively; ≐ should be read as ‘is equal to, up to smaller‐order terms’, and ≈ as ‘has exact (asymptotic) rate/order of’; random and non‐random (column) vectors are typeset as Z=(Z1,Z2,) and z=(z1,z2,), respectively, with random and non‐random matrices Z̲ and z̲, and scalar random variables and values Z and z .…”
Section: Introductionmentioning
confidence: 99%
“…With a simulation study, they showed that Hutson's method performed at least as well as Beran and Hall's, in terms of confidence interval coverage and short interval widths. Their method also performed similarly to Beran and Hall's and better than the bootstrap method (see Goldman & Kaplan, , p. 337–338). Chapter 5 in Meeker et al () also contains some discussion of interpolation methods.…”
Section: Quantile Confidence Interval Construction Methodsmentioning
confidence: 74%
“…Goldman and Kaplan () applied a calibration method similar to Ho and Lee's () to Hutson's () procedure to improve the asymptotic performance of the confidence intervals. As with Hutson (), the method cannot be applied for extreme order statistics in some cases.…”
Section: Quantile Confidence Interval Construction Methodsmentioning
confidence: 99%
“…This CDF can be computed immediately by any modern statistical software. The only difficulty is if a specific α is desired for a specific τ , in which case one cannot find an exact, non-randomized test (but for solutions using interpolation, see Beran and Hall, 1993;Goldman and Kaplan, 2017a).…”
Section: Basic Method Fwer and Computationmentioning
confidence: 99%